2022
DOI: 10.1002/chem.202200524
|View full text |Cite
|
Sign up to set email alerts
|

A Universal DNA Aptamer that Recognizes Spike Proteins of Diverse SARS‐CoV‐2 Variants of Concern

Abstract: What is the most significant result of this study?This study reports on au nique DNA aptamer,d enoted MSA52, that displays auniversally high affinityfor the spike proteins of wildtype SARS-CoV-2 as well as the Alpha, Beta, Gamma, Epsilon, Kappa, Delta, and Omicron variants. This aptamer also recognizes pseudotyped lentiviruses (PL) expressing eight different spike proteins of SARS-CoV-2 with K d values between 20-50 pM. It was integrated into as imple colorimetric assay for the detection of multiple PL variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The aptamer used for this work is MSA52, a monomeric DNA aptamer (Figure B) discovered by us through selection with variant S proteins . Impressively, MSA52 was found to universally recognize variants that were not analyzed in the original selection experiment, demonstrating that the aptamer is insensitive to emerging S protein mutations . Hence, MSA52 is an ideal candidate for COVID-19 recognition, and the trimerization of this MRE should enhance its complementarity to and affinity for the S protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aptamer used for this work is MSA52, a monomeric DNA aptamer (Figure B) discovered by us through selection with variant S proteins . Impressively, MSA52 was found to universally recognize variants that were not analyzed in the original selection experiment, demonstrating that the aptamer is insensitive to emerging S protein mutations . Hence, MSA52 is an ideal candidate for COVID-19 recognition, and the trimerization of this MRE should enhance its complementarity to and affinity for the S protein.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of a T15 linker was made for the following reasons. First, MSA52 has been shown to bind to the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein. , Second, it has been demonstrated that the distance between RBD subunits on the spike protein trimer ranges from 2.7 to 7.4 nm, considering the “closed” and “open” conformational states of the RBD. Third, our calculations indicate that each arm of the trebler-linked trimeric aptamer with a 15-thymine linker has a persistence length of 6.9 nm .…”
Section: Resultsmentioning
confidence: 99%
“…We compared the sequence of SCORe to other aptamers reported to bind the SARS-CoV-2 S protein at the RBD (CoV-2-RBD-1C, CoV-2-RBD-4C, CoV-2-6C3, nCoV-S1-Apt1, MSA5, and MSA52-T5) ,, and found no similarity between SCORe and the other sequences when compared with local alignment (Figure S4). …”
Section: Resultsmentioning
confidence: 99%
“… 15 Most of the currently reported aptamers were selected against wild-type or alpha variant S protein. 13 , 16 19 To the best of our knowledge, only the Li group has reported a DNA aptamer that binds to BA.1 S protein 20 that does not also bind nonspecifically to His-tag-containing proteins ( Figure S1A ). We tested literature-reported S-binding aptamers (SP6.51, 18 SNAP1, 13 SNAP4.74, 14 CoV-2-4C, 19 CoV-2-6C3 21 ), including two discovered by our group, but none of these aptamers show specific binding to BA.1 NTD or S1 protein ( Figure S1 ) in our testing conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation